Arctic freshwater outflow suppressed Nordic Seas overturning and oceanic heat transport during the Last Interglacial - Mohamed M. Ezat; Kirsten Fahl; Tine L. Rasmussen (Nature Communications)
Abstract The Last Interglacial period (LIG) was characterized by a long-term Arctic atmospheric warming above the preindustrial level. The LIG thus provides a case study of Arctic feedback mechanisms of the cryosphere-ocean circulation-climate system under warm climatic conditions. Previous studies suggested a delay in the LIG peak warming in the North Atlantic compared to the Southern Ocean and evoked the possibility of southward extension of Arctic sea ice to the southern Norwegian Sea during the early LIG. Here we compile new and published proxy data on past changes in sea ice distribution, sea surface temperature and salinity, deep ocean convection, and meltwater sources based on well-dated records from the Norwegian Sea. Our data suggest that southward outflow of Arctic freshwater supressed Nordic Seas deep-water formation and northward oceanic heat transport during the early LIG. These findings showcase the complex feedback interactions between a warming climate, sea ice, ocean circulation and regional climate.